2019
DOI: 10.1039/c9cp00790c
|View full text |Cite
|
Sign up to set email alerts
|

Low linear energy transfer radiolysis of supercritical water at 400 °C: in situ generation of ultrafast, transient, density-dependent “acid spikes”

Abstract: An abrupt, temporary and highly acidic pH response (“acid spikes”) is observed around the “native” radiation tracks for all considered densities immediately after irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…35 We calculated the yields (or G-values) 36 and the concentrations of radiolytically formed H 3 O + and the corresponding pH values that prevailed in these track regions immediately after irradiation as a function of time for both low and high LET, 16,25 at ambient and elevated temperatures, 37 even under supercritical conditions. 38,39 In all cases studied, an abrupt, transient acidspike response was observed around the "native" radiation tracks. This response is a very sensitive function of radiation quality (LET) and temperature.…”
Section: The Early Transitory Acidic Ph Responsementioning
confidence: 89%
“…35 We calculated the yields (or G-values) 36 and the concentrations of radiolytically formed H 3 O + and the corresponding pH values that prevailed in these track regions immediately after irradiation as a function of time for both low and high LET, 16,25 at ambient and elevated temperatures, 37 even under supercritical conditions. 38,39 In all cases studied, an abrupt, transient acidspike response was observed around the "native" radiation tracks. This response is a very sensitive function of radiation quality (LET) and temperature.…”
Section: The Early Transitory Acidic Ph Responsementioning
confidence: 89%
“…Through the modeling work, the researchers found that during the radiolysis of uranium hexafluoride, production of uranium pentafluoride occurs and the yield is 1 * 10 −7 of the original concentration of hexafluoride. Patwary et al (2019) explored the radiolysis of supercritical water at 400 °C using low linear energy transfer based on Monte Carlo simulation. The study mentioned that, in the range of 0.15 − 0.6 g∕cm 3 , the duration and extent of the acidic pH depends on water density.…”
Section: Impact Of Radiolysismentioning
confidence: 99%
“…Patwary et al (2019) explored the radiolysis of supercritical water at 400 °C using low linear energy transfer based on Monte Carlo simulation. The study mentioned that, in the range of 0.150.6g/cm3, the duration and extent of the acidic pH depends on water density.…”
Section: Impact Of Radiolysismentioning
confidence: 99%